2014
DOI: 10.1158/0008-5472.can-13-1070
|View full text |Cite
|
Sign up to set email alerts
|

p53 and NF-κB Coregulate Proinflammatory Gene Responses in Human Macrophages

Abstract: Macrophages are sentinel immune cells that survey the tissue microenvironment, releasing cytokines in response to both exogenous insults and endogenous events such as tumorigenesis. Macrophages mediate tumor surveillance and therapy-induced tumor regression; however, Tumor Associated Macrophages (TAMs) and their products may also promote tumor progression. Whereas NF-κB is prominent in macrophage-initiated inflammatory responses, little is known about the role of p53 in macrophage responses to environmental ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
152
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(166 citation statements)
references
References 49 publications
(74 reference statements)
12
152
2
Order By: Relevance
“…Recent studies have shown that TAM-like PBMo-derived macrophages stimulated with TCM such as those found in breast, ovarian, and colorectal cancer produced these factors. 16,[38][39][40] In the present study, GDF15 was upregulated in PBMo-derived macrophages stimulated with TECM, whereas, to our knowledge, it has not been reported that TAM-like PBMo-derived macrophages stimulated with other TCMs secreted GDF15. Expression of GDF15 was not detected in cytokine-induced M2-polarized macrophages such as IL-4 and IL-13 (Supplementary Figure 1).…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggercontrasting
confidence: 70%
“…Recent studies have shown that TAM-like PBMo-derived macrophages stimulated with TCM such as those found in breast, ovarian, and colorectal cancer produced these factors. 16,[38][39][40] In the present study, GDF15 was upregulated in PBMo-derived macrophages stimulated with TECM, whereas, to our knowledge, it has not been reported that TAM-like PBMo-derived macrophages stimulated with other TCMs secreted GDF15. Expression of GDF15 was not detected in cytokine-induced M2-polarized macrophages such as IL-4 and IL-13 (Supplementary Figure 1).…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggercontrasting
confidence: 70%
“…Inflammatory responses to exposures of p53-activating chemotherapeutic drugs were measured in immune cells from the blood and lungs of healthy volunteers [124]. Various proinflammatory genes had enhanced expression after exposure to the chemotherapeutics which required both p53 and NF-κB.…”
Section: Targeting Constituents Within the Tumor Microenvironmentmentioning
confidence: 99%
“…4. Various nanoformulations for co-delivery of therapeutics with normalized pharmacokinetics and pharmacodynamics, including self-assembled nanoscale coordination polymer [158], cholesterol-based chimeric nanoparticle [157], thermosensitive hydrogel [123], mesoporous silica nanoparticle [125], and liposomes [124].…”
Section: Combined Gene and Chemotherapymentioning
confidence: 99%
“…Indeed, recent reports suggest that p53 may indeed have such a role to play in TAM biology. 19,20 A low concentration of endotoxin triggers tolerance, which involves the reprogramming of macrophages. 21 Prior exposure to endotoxin can be an evolutionary advantage because it triggers a selective shutdown of the production of proinflammatory cytokines (from M1 macrophages), which cause tissue damage and preserves the generation of protective antiinflammatory mediators (from M2 macrophages).…”
Section: Figure 7 (Continued)mentioning
confidence: 99%